Routine colonoscopy may be needed for uncomplicated acute right colonic diverticulitis - Kil-yong Lee; Jaeim Lee; Youn Young Park; Seong Taek Oh (BMC Gastroenterology, 2021)
Abstract Background Routine colonoscopy is recommended to determine the coexistence of colon cancer after medical treatment for colon diverticulitis. However, in the case of uncomplicated diverticulitis diagnosed by computed tomography, the clinical relevance of routine follow-up colonoscopy has recently been debated. Yet, the role of follow-up colonoscopy for right colon diverticulitis, which tends to develop at a younger age than left colon diverticulitis, has not been specifically evaluated. Therefore, we aimed to evaluate the incidence of right colon cancer or colonic adenomatous polyps, detected by routine colonoscopy, after conservative management of acute uncomplicated right colon diverticulitis. Methods Patients with uncomplicated right colon diverticulitis (modified Hinchey stage Ia) diagnosed by computed tomography imaging, between 2011 and 2017, and who underwent follow-up colonoscopy surveillance after treatment were included. The primary outcome was the incidence of colon cancer, with the detection rate of adenoma being the secondary outcome. Information for analysis was retrieved retrospectively from patients’ medical records. Results The study group included 330 consecutive patients, with a mean age of 41.9 years, and 51.9% being men. For the primary outcome, the rate of colon cancer on follow-up colonoscopy was 0.3% (1/330 cases). The rate of adenoma detection was 20.9% (69/330 cases) and advanced adenoma (> 10 mm in diameter; or exhibiting a > 25% villous component or severe dysplasia), including colon cancer, was observed in 9 patients (2.7%). Conclusions In patients with acute uncomplicated right colonic diverticulitis, routine colonoscopy after conservative treatment may be necessary because although the colon cancer detection rate is low, it is possible to detect advanced colon adenoma.